Expression and behavior of the solutions of some rational recursive sequences. (22nd April 2016) - Elsayed, E. M.
Abstract : We obtain in this paper the expression of the solutions of the following recursive sequences: x n + 1 = x n − 3 x n − 4 x n ( ± 1 ± x n − 1 x n − 2 x n − 3 x n − 4 ), n = 0, 1, …, where the initial conditions are arbitrary real numbers. Also, we study the behavior of the solution of these equations. Copyright © 2016 John Wiley & Sons, Ltd.